No impact of disseminated intravascular coagulation in kidney donors on long‐term kidney transplantation outcome: A multicenter propensity‐matched study. Issue 2 (23rd August 2018) - Garrouste, Cyril; Baudenon, Julien; Gatault, Philippe; Pereira, Bruno; Etienne, Isabelle; Thierry, Antoine; Szlavik, Nora; Aniort, Julien; Rabant, Marion; Lambert, Céline; Sayegh, Johnny; Oniszczuk, Julie; et al.
Abstract : The diagnosis of disseminated intravascular coagulation (DIC) is often considered to be a contraindication to organ donation. The aim of this study was to evaluate the impact of DIC+ donors on kidney recipient (KR) evolution. We identified 169 KRs with DIC+ donation after brain death donors between January 1996 and December 2012 in 6 French transplant centers. Individuals were matched using propensity scores to 338 recipients with DIC− donors according to donor age and sex, whether expanded criteria for the donor existed, graft year, and transplantation center. After kidney transplantation, delayed graft function was observed in 28.1% of DIC+ KRs and in 22.8% of DIC− KRs (NS). Renal allograft survival at 1, 5, and 10 years was 94.5%, 89.3%, and 73.9% and 96.2%, 90.8%, and 81.3% in DIC+ KRs and DIC− KRs, respectively (NS). The median estimated glomerular filtration rate (eGFR) was similar between DIC+ and DIC− KRs at 3 months, 1 year, and 10 years: 45.9 vs 48.1 mL/min, 42.1 vs 43.1 mL/min, and 33.9 vs 38.1 mL/min, respectively. Delayed calcineurin inhibitor introduction or induction had no impact on delayed graft function rate or eGFR evolution at 10 years after transplantation in DIC+ KRs. Donor DIC did not seem to affect initial outcome, long‐term graft function, or allograft survival. Abstract : In this multicenter propensity‐matched study, the authors find no impact of disseminated intravascular coagulation on initial outcome, long‐term graft function, or allograft survival, despite it classically being a contraindication for kidney donation.